Constraints in livestock service delivery through mobile veterinary units (MVUs): Evidence from Odisha - JENA, ANUPAMA; CHANDER, MAHESH; BARDHAN, D (The Indian Journal of Animal Sciences, 2017)
India has enormous livestock resources, production and productivity of Indian livestock remains low due to several factors including poor livestock service delivery. Towards improving the delivery of livestock services, Mobile Veterinary Unit (MVU) appears an innovative way of animal health service delivery at farmers' doorstep. The MVUs set up with funding under Rastriya Krishi Vikas Yojana (RKVY), are currently operational in all the 314 blocks of Odisha. This study was undertaken in Kandhamal district of Odisha during 2016, to analyse the functioning of MVUs including the constraints faced by the farmers as well as the service providers (Veterinary Officers and Livestock Inspectors) in delivering the animal health services through MVUs. The study revealed that limited frequency of service, limited staff in the MVUs, lack of awareness towards importance of service among farmers, less number of awareness camps, short service delivery period and very less remuneration to MVU professionals were the major constraints reported by the farmers and service providers. This study, thus, suggests that the MVUs could be more successful in improving the animal health service delivery in rural Odisha, if these constraints are overcome.